2019
DOI: 10.1093/jpepsy/jsz055
|View full text |Cite
|
Sign up to set email alerts
|

From Diagnoses to Ongoing Journey: Parent Experiences Following Congenital Heart Disease Diagnoses

Abstract: Despite improved survival among children with congenital heart disease (CHD), the risk of psychosocial difficulties remains largely unchanged with an increased emphasis of improving support for parents as a mechanism to optimize outcomes. Objective Using qualitative and quantitative methods, the current cross-sectional study examined parents' experiences at the time of their child's diagnosis, what they thought helped their child recover, barriers to support,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Parents included in our study experienced loss in confidence in themselves and their children. These findings coincide with results by many other researchers reporting that parents of children with complex CHD undergo intense emotional stress, anxiety, and perceive hopelessness [ 15 , 34 37 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Parents included in our study experienced loss in confidence in themselves and their children. These findings coincide with results by many other researchers reporting that parents of children with complex CHD undergo intense emotional stress, anxiety, and perceive hopelessness [ 15 , 34 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although this reaction is very understandable, one could argue that parents tend to overprotect their CHD children, which might lead to short and longer-term developmental risks: Could motor delay in CHD children be partially due to parents’ overprotectiveness and their fear of over-straining their children during physical activities? Majnemer et al [ 42 ] and Williams et al [ 15 ] support this assumption. Our participating parents reported that they tended to handle their children very carefully, to avoid uncomfortable positions such as prone, and to watch their children constantly.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The mothers of children with CHD (aged 7 months to 14 years) commented on the burden of childcare and tension resulting from the disease and difficulties of the care process [ 13 ]. In addition, mothers of children with CHD (between 6 months and 4 years) described their appreciation of the healthcare team on initial diagnosis, their possible optimism surrounding medical outcomes, and feelings of general uncertainty concerning the child’s upcoming medical care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%